GIS fundamentals - Wise, Stephen (Boca Raton : CRC Press, 2014)
"Aimed at readers with a knowledge of Geographic Information Systems (GIS) but no formal training in computer science, this book provides a clear and accessible introduction to how GIS store and process spatial data. This updated edition includes two new chapters on databases and future developments, substantial additional material on raster imagery, and revisions throughout that incorporate up-to-date applications such as GPS on mobile devices and Internet-based services. The chapter on future technologies includes discussions of 3D GIS, handling time in GIS, spatial SQL, and handling imprecise geographies"--
Includes index.
Glossary: p. 297-303.
Includes bibliographical references and index.
Keywords: Geographic information systems; Geospatial data